Pembinaan Warga Gereja Terhadap Etika Pebisnis Warga Gereja Masehi Injili Talaud Jemaat Lembong Rintulu Mamahan Kabupaten Kepuluan Talaud - Anjelia Tundu; Semuel Selanno (Peneliti.net, 2023)
The purpose of this study is to describe how the business behavior of the church residents of the Germita Lembong Ritulu Mamahan Church is based on Christian ethics. Analyze the factors that encourage and inhibit the ethical behavior of business people from church residents of the Germita Lembong Rintulu Mamahan Church. Describe how the church community fosters business ethics in the Germita Lembong Rintulu Mamahan Church. This research is a quality research with a phenologic approach. Data collection is done through interviews, observation, and documentation. From the findings of the study, there are indications below: (1) the behavior of business people from church residents has not all behaved well based on Christian ethics. (2) factors that encourage the ethical behavior of business people from church citizens are factors of Christian religious values. (3) factors that hinder the ethical behavior of business people from church citizens are: having a bad relationship with God, poor character of business people, and lack of coaching church citizens towards business people (4) coaching church citizens towards business people only through the service of God's word in every worship meeting